Changes in the composition of gut and vaginal microbiota in patients with postmenopausal osteoporosis - Yang, Xueli; Chang, Tian; Yuan, Qian; Wei, Wei; Wang, Pingping; Song, Xiaojian; Yuan, Huijuan (Frontiers in Immunology, 2022)
Background: Postmenopausal osteoporosis (PMO) is influenced by estrogen metabolism and immune response, which are modulated by several factors including the microbiome and inflammation. Therefore, there is increasing interest in understanding the role of microbiota in PMO. Objectives: To investigate variations in gut microbiota (GM) and vaginal microbiota (VM) in postmenopausal women with osteoporosis. Methods: A total of 132 postmenopausal women were recruited for the study and divided into osteoporosis (n = 34), osteopenia (n = 47), and control (n = 51) groups based on their T score. The serum levels of interleukin (IL)-10, tumor necrosis factor (TNF)-α, and lipopolysaccharide-binding protein were determined via enzyme-linked immunosorbent assay. Additionally, 16S rRNA gene V3-V4 region sequencing was performed to investigate the GM and VM of the participants. Results: Significant differences were observed in the microbial compositions of fecal and vaginal samples between groups (p < 0.05). It was noted that for GM, Romboutsia, unclassified_Mollicutes, and Weissella spp. were enriched in the control group, whereas the abundances of Fusicatenibacter, Lachnoclostridium, and Megamonas spp. were higher in the osteoporosis group than in the other groups. Additionally, for VM, Lactobacillus was enriched in the control group, whereas the abundances of Peptoniphilus, Propionimicrobium, and Gallicola spp. were higher in the osteoporosis group than in the other groups. The predicted functional capacities of GM and VM were different in the various groups. We also found that the serum level of IL-10 in the osteoporosis group was significantly lower than that in the control group and osteopenia group, while TNF-α was significantly higher in the osteoporosis group than that in the control group (p < 0.05). Conclusion: The results show that changes in BMD in postmenopausal women are associated with the changes in GM and VM; however, changes in GM are more closely correlated with PMO than VM.